Binding pathway of histamine to the hH4R, observed by unconstrained molecular dynamics. Issue 6 (15th March 2015) - Wittmann, Hans-Joachim; Strasser, Andrea
Graphical abstract: Abstract: Histamine binds with high affinity to the human histamine H4 receptor (hH4 R). We are the first to examine the complete binding pathway of histamine from the extracellular side to the orthosteric binding site of the hH4 R by means of unconstrained molecular dynamic simulation. Furthermore, the simulations show that the positively charged amine moiety of the histamine interacts electrostatically with the highly conserved Asp 3.32, while the imidazole moiety forms a hydrogen bond interaction with Glu 5.46 and Gln 7.42 .